2020
DOI: 10.1097/aln.0000000000003096
|View full text |Cite|
|
Sign up to set email alerts
|

Lung Ultrasound in Emergency and Critically Ill Patients

Abstract: Background Lung ultrasound is increasingly used in critically ill patients as an alternative to bedside chest radiography, but the best training method remains uncertain. This study describes a training curriculum allowing trainees to acquire basic competence. Methods This multicenter, prospective, and educational study was conducted in 10 Intensive Care Units in Brazil, China, France and Uruguay. One hundred residents, respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 27 publications
(49 reference statements)
4
46
0
3
Order By: Relevance
“…Secondly, the application of point-of-care ultrasound is operator-dependent, and requires basic training. Even so, learners have found that it is not difficult to acquire basic lung ultrasound skills over a short period of time, with a minimum required number of 25 supervised scans ( 28 ) .…”
Section: Discussion and Brief Review Of Current Literaturementioning
confidence: 99%
“…Secondly, the application of point-of-care ultrasound is operator-dependent, and requires basic training. Even so, learners have found that it is not difficult to acquire basic lung ultrasound skills over a short period of time, with a minimum required number of 25 supervised scans ( 28 ) .…”
Section: Discussion and Brief Review Of Current Literaturementioning
confidence: 99%
“…The basics can be learned in under two hours. [37][38][39] Limitations/bias Our study has some important limitations. First, this was an observational study; no blinding, randomization or power calculation was performed.…”
Section: Strengthsmentioning
confidence: 96%
“…Thus, we imaged the posterior areas behind the posterior axillary line rather than in the paravertebral areas to avoid turning completely the patient [20]. LUS examinations were performed by emergency physicians or intensivists in charge of the patient [21,22]. The skill of the operators was rated as follows [21]:…”
Section: Lus and Chest Ct Examinationmentioning
confidence: 99%
“…LUS examinations were performed by emergency physicians or intensivists in charge of the patient [21,22]. The skill of the operators was rated as follows [21]:…”
Section: Lus and Chest Ct Examinationmentioning
confidence: 99%